2010
DOI: 10.1071/ah08700
|View full text |Cite
|
Sign up to set email alerts
|

The impact of recent physiotherapy graduates in the workforce: a study of Curtin University entry-level physiotherapists 2000 - 2004

Abstract: Physiotherapy is the largest healthcare contributor after nursing and medicine and it is important to understand its employment characteristics. This study aimed to explore workforce trends for recent physiotherapy graduates, including satisfaction and motivating factors, and future career intentions. A self-administered questionnaire was provided to contactable entry-level physiotherapy graduates (2000-2004) from Curtin University. Of 256 respondents (62.9%), 76.5% were employed full-time. A total of 45% of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
52
1
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(55 citation statements)
references
References 15 publications
0
52
1
2
Order By: Relevance
“…Previous studies have reported that the majority of physiotherapists in this demographic expect to have short-term careers of 10 years or less (2,3). When participants in all three focus groups reflected on the attrition rate of early career physiotherapists they identified a lack of peer support and mentoring as a key factor in driving colleagues away from private practice.…”
Section: Discussionmentioning
confidence: 86%
See 3 more Smart Citations
“…Previous studies have reported that the majority of physiotherapists in this demographic expect to have short-term careers of 10 years or less (2,3). When participants in all three focus groups reflected on the attrition rate of early career physiotherapists they identified a lack of peer support and mentoring as a key factor in driving colleagues away from private practice.…”
Section: Discussionmentioning
confidence: 86%
“…Increasingly, graduates are being employed into private practice positions yet recent studies indicate that physiotherapy graduates predict short careers (2,3). Only 23% of physiotherapy graduates from Curtin University in Western Australia predicted a career of greater than 20 years, with 65% predicting a career of 10 years or less (3).…”
Section: Introduction/backgroundmentioning
confidence: 99%
See 2 more Smart Citations
“…[5][6][7][8][9][10][11] Finding work adequately challenging has been identified as a factor that exists on a continuum with perceived lack of or extreme challenge being negative influences. 5,10,12,13 The opportunity to perform additional workplace duties and extend workplace roles, has also been recognised as an influential factor on job satisfaction. 14 This may be related to the challenge provided by these extra duties.…”
Section: Introductionmentioning
confidence: 99%